2015
DOI: 10.1186/s11671-015-0755-0
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, optical properties, and catalytic performance of Cu2O-modified ZnO nanorods prepared by electrodeposition

Abstract: Cu2O-modified ZnO nanorods are prepared by a two-step electrodeposition method on ITO substrates, and the deposition time of Cu2O is 0, 1, 5, and 10 min, respectively. Cu2O particles are embedded in the interspaces of the ZnO nanorods, and the amounts of the Cu2O particles increase obviously when the deposition time lasts longer. The peaks corresponding to ZnO nanorods and Cu2O particles are detected from scanning electron microscope (SEM) and X-ray diffraction (XRD) results. UV-vis absorption spectra measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…From the obtained results, it is evident that when subjected to different calcination temperatures, the prepared nanocomposites expound different morphology, structural properties and crystallinity. Researchers such as Zhang et al [32], Jiang et al [10] and Chen [29, 31] found results slightly different to those obtained in this paper [23, 3337], thus, confirming a significant and superior green synthetic route.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…From the obtained results, it is evident that when subjected to different calcination temperatures, the prepared nanocomposites expound different morphology, structural properties and crystallinity. Researchers such as Zhang et al [32], Jiang et al [10] and Chen [29, 31] found results slightly different to those obtained in this paper [23, 3337], thus, confirming a significant and superior green synthetic route.…”
Section: Resultscontrasting
confidence: 67%
“…The production of copper and zinc nanocomposite with controllable sizes, shapes and surface properties is vital for exploring copper-zinc-based nano-oxides for different applications. There are numerous reports on chemically and physically prepared nanocrystalline copper-zinc based oxides [1, 10, 15, 20]. Deraz et al reported the synthesis and characterisation of new copper-based nanocomposite using glycine-assisted combustion method [7] while in his paper (Habibi et al) [21] fabricated and characterised ternary CuO-ZnO-Cu 2 O nanocomposites by Sol-Gel Route at different temperatures [22].…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum in Figure 7A shows that the Cu 2p 3/2 and Cu 2p 1/2 peaks are located at approximately 934 eV and 954 eV, respectively, with a shake-up peak at~943 eV for all materials. The existence of these peaks confirms the presence of Cu 2+ in the catalyst [44]. It is well reported that Cu may exist in the form of CuO [45,46].…”
Section: Effect Of Copper Loading On Zif-8supporting
confidence: 65%
“…A plausible explanation of these characteristics is due to the existence of the V O and Zn I excitation state, which further provides the wider energy range absorption of light. Previously, low band gap ZnO was reported in other studies, where optical absorption of the ZnO is presented [ 38 ]. The decrease of band gap was promoted by the presence of the midgap state in doped ZnO system [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 98%